Determining a Standard for Number of Viewers of Educational Programs Delivered Through Government Access Cable TV - M. F. Smith; Judy Yates (Journal of Applied Communications, 1990)
Government access cable television is being used more and more to reach diverse audiences. However, the methodology to determine how many viewers are tuning in to such programs is piece-meal with the pieces not interconnecting to form a complete process. The paper explains the methodology used to estimate number of viewers for one television series which airs a new program each week with the same program appearing three times a day for a total of 15 showings each week. Three procedures were used to arrive at an overall estimate: telephone survey of cable subscribers. questioning a sample of first-time callers and visitors to the Extension office as to how they learned about the office. and synthesis and application of a number of studies described in the literature. The three procedures together provide what is believed to be a more accurate estimation of number of viewers than anyone by itself: and all are applicable to other Similar television series.